IMPROVING LEARNING OUTCOMES THROUGH THE PICTURE AND PICTURE MODEL INTEGRATED WITH WORDWALL IN IPAS FOR GRADE IV STUDENTS - Melda Oktika Ginting; Hendrikson R Panjaitan (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2026)
This study aims to improve students’ learning outcomes through the Picture and Picture learning model integrated with the Wordwall application in the IPAS subject for fourth-grade students. The research employed a quantitative approach with a pre-experimental design (one-group pretest–posttest design). The sample consisted of all 28 students in Class IVA at SD Negeri 101740 Tanjung Selamat, comprising 9 male and 19 female students. Data were collected using learning achievement tests administered before and after the intervention, as well as observation and documentation techniques. The collected data were then analyzed quantitatively. The findings indicate that the use of Wordwall significantly improved students’ learning outcomes, as evidenced by the increase in mean scores from the pretest to the posttest. This improvement reflects a higher level of understanding of the instructional material. Furthermore, the integration of the Picture and Picture model with Wordwall was effective and engaging, fostering interactive learning through visual representations and digital quiz activities. Students demonstrated greater participation, focus, and enthusiasm during lessons. In addition to enhancing conceptual understanding, the model also supported the development of students’ critical thinking and collaborative skills. In conclusion, the Picture and Picture model supported by the Wordwall application can serve as an effective alternative instructional strategy for improving students’ learning outcomes.